ANALISIS KEEFEKTIFAN IMPLEMENTASI GAME BASED LEARNING BERBASIS WORDWALL UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR SISWA MATERI SISTEM EKSKRESI MANUSIA DI MAS PP BINA ULAMA - Wulansari, Anggi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research is motivated by the need for comprehensive and engaging learning methods for the complex human excretory system material, where conventional approaches are less capable of developing students' higher-order thinking skills. The study aims to analyze the effectiveness of Wordwall-based game-based learning implementation in improving students' thinking abilities on human excretory system material at MAS PP Bina Ulama. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design involving 59 eleventh-grade students divided into an experimental class (n=30) using Wordwall and a control class (n=29) using conventional methods. Results showed that the implementation of Wordwall-based GBL effectively improved students' thinking abilities with an N-gain of 0.76 (high category) compared to the control class at 0.48 (medium category), with significant differences (t=8.925; p<0.05; Cohen's d=1.64). The highest improvement occurred in analytical thinking skills (C4) with an N-gain of 0.83. It is concluded that Wordwall-based GBL effectively enhances students' higher-order thinking skills and is compatible with the characteristics of Islamic boarding school education, thus recommended as an alternative innovative learning strategy to optimize learning within time constraints. Keywords: Game-based learning, Wordwall, higher-order thinking skills, excretory                  system, Islamic boarding school education Abstrak: Penelitian ini dilatarbelakangi oleh kebutuhan metode pembelajaran komprehensif dan menarik pada materi sistem ekskresi manusia yang kompleks, di mana pendekatan konvensional kurang mampu mengembangkan kemampuan berpikir tingkat tinggi siswa. Tujuan penelitian adalah menganalisis keefektifan implementasi game based learning berbasis Wordwall dalam meningkatkan kemampuan berpikir siswa pada materi sistem ekskresi manusia di MAS PP Bina Ulama. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi eksperimen nonequivalent control group design melibatkan 59 siswa kelas XI yang dibagi menjadi kelas eksperimen (n=30) menggunakan Wordwall dan kelas kontrol (n=29) menggunakan metode konvensional. Hasil menunjukkan bahwa implementasi GBL berbasis Wordwall efektif meningkatkan kemampuan berpikir siswa dengan N-gain 0,76 (kategori tinggi) dibandingkan kelas kontrol 0,48 (kategori sedang), dengan perbedaan signifikan (t=8,925; p<0,05; Cohen's d=1,64). Peningkatan tertinggi terjadi pada aspek kemampuan menganalisis (C4) dengan N-gain 0,83. Disimpulkan bahwa GBL berbasis Wordwall efektif meningkatkan kemampuan berpikir tingkat tinggi siswa dan kompatibel dengan karakteristik pendidikan pesantren, sehingga direkomendasikan sebagai alternatif strategi pembelajaran inovatif untuk mengoptimalkan pembelajaran dalam keterbatasan waktu. Kata kunci: Game based learning, Wordwall, kemampuan berpikir tingkat tinggi, sistem ekskresi, pendidikan pesantren